The European Neighbourhood Policy: Conditionality revisited for the EU's Eastern Neighbours - Sasse, G (Routledge, 2008)
The European Neighbourhood Policy (ENP) is modelled on the institutional and procedural experience of the EU's eastward enlargement, although it explicitly excludes a membership perspective. It thus aims to define an alternative incentive for domestic reform in neighbouring countries, referred to as 'a stake in the internal market'. This article suggests that the ENP amounts to a form of 'conditionality-lite' for non-candidate countries. Within the ENP the key defining elements of conditionality—clear incentive and enforcement structures—are vague for both the EU and its neighbouring countries. Thus, the ENP is conceptually and empirically weak when measured against a simple, rationalist conditionality model. In line with the alternative understanding of conditionality as a process rather than a clear-cut variable, the main function of the ENP is twofold: it provides an external reference point which domestic political actors in the ENP countries can choose to utilise when it fits their agenda (both pro-EU or anti-EU); and a loose framework for socialisation. This process of socialisation involves both the EU and the ENP countries. Through an analysis of the ENP process in Ukraine and Moldova it concludes that while the ENP tries to prevent a repeat of the EU's 'rhetorical entrapment' in further eastward enlargement, it paradoxically paves the way for a 'procedural entrapment' in ENP countries that harbour membership aspirations and provides a momentum, though not a guarantee, for conflict resolution.